WOMEN'S LEADERSHIP STRATEGY IN INCREASING COMPETITIVENESS IN EDUCATIONAL INSTITUTIONS SMK AL-KALAM BANI MARWAN LEBAK REGENCY - Taufiqurrahman Taufiqurrahman; Annisa Nabilah; Zahruddin Zahruddin; Jejen Musfah (Program Studi PGSD Universitas Flores, 2023)
This study describes the strategy of women's leadership in increasing competitiveness in the AL-Kalam Vocational School, Lebak Regency. Principals as leaders of educational institutions need to renew strategies in dealing with educational competitiveness. The method used in this research is descriptive qualitative with a case study approach. Data collection techniques in this study are through observation, in-depth interviews and documentation. Activities in data analysis are: data reduction, data display, and conclusion drawing/verification. The results showed that there were 9 strategies for female school principals in dealing with or increasing competitiveness, namely: pricing strategies, promotion strategies, improving school management, providing training for teachers, carrying out learning innovations, creating school character or characteristics, working with the industrial business world, hospitality and good communication.